Terrorism and counterterrorism - Nacos, Brigitte Lebens (Routledge, Taylor & Francis Group, 2016)
In this comprehensive and highly readable text, renowned expert Brigitte Nacos clearly defines terrorism's diverse causes, actors, and strategies; outlines anti- and counter-terrorist responses; and highlights terrorism's relationship with the public and media. Terrorism and Counterterrorism introduces students to the field's main debates and helps them critically assess our understanding of, and our strategies for, addressing this complex and enduring issue.